2014
DOI: 10.1179/2045772313y.0000000180
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and adherence to the 2010 Dietary Guidelines for Americans among individuals with chronic spinal cord injury: A pilot study

Abstract: Objective: To investigate dietary intake and adherence to the 2010 Dietary Guidelines for Americans in individuals with chronic spinal cord injury (SCI) and able-bodied individuals. Design: A pilot study of dietary intake among a sample of individuals with SCI >1 year ago from a single site compared with able-bodied individuals. Participants/methods: One hundred black or white adults aged 38-55 years old with SCI >1 year and 100 age-, sex-, and race-matched adults enrolled in the Coronary Artery Risk Developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 89 publications
(85 reference statements)
1
39
0
Order By: Relevance
“…Moreover, an excessive intake of food may affect the normal intestinal function. Thus, an appropriate dietary management is needed for patients with SCI [30–32]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an excessive intake of food may affect the normal intestinal function. Thus, an appropriate dietary management is needed for patients with SCI [30–32]. …”
Section: Discussionmentioning
confidence: 99%
“…Despite this knowledge, it has been shown that persons with SCI have a poor quality diet characterized by inadequate intake of dairy, fruit, whole grain foods and fibre, and a too high intake of fat [29,30]. In persons with LLA, the intake of total fat, saturated fat, sugar and sodium have been shown to be higher than recommended [15].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a healthy diet is recommended in SCI individuals, there is a substantial lack of nutritional guidelines for these patients (71-73). In addition, their altered body composition limits the accurate measurement of the energy intake and the need (74,75). A recent systematic review and meta-analysis investigated the nutritional status of adult subjects with chronic SCI (76,77).…”
Section: Nutritional Interventionsmentioning
confidence: 99%